The Effect Of Debt On Residual Business Results - Nabu, Herti; Susilawati , Made; Selan, Dwi Dersmi (GOVERNORS, 2025)
The purpose of this study is to determine the extent of the influence of debt on the remaining operating results of the Kopdit Swasti Sari Kupang Savings and Loan Cooperative in 2021-2023. The method used in this study is descriptive quantitative using simple linear regression analysis techniques. The population and sample in this study are all financial statements of debt and SHU of the Swasti Sari Cooperative from 2021-2023. The data sources in this study use primary and secondary data. Data collection techniques in this study are interviews, documentation and literature studies. This research was conducted at the Swasti Sari Kupang Savings and Loan Cooperative using data analysis techniques are financial report data from 2021-2023. The variables used in this study are Debt (X) and Operating Surplus (Y). Data processing in this study uses SPSS Version 21. The results of the study obtained a regression equation Y= 2046383657.698+,001 bX, meaning that each factorincrease of one rupiah in total debt (X) will increase the SHU value by 0.001 rupiah and the value is significant for total debtis 0.047 which shows that total debt has a significant influence on SHU because the significance value is less than 0.05.